1995
DOI: 10.1093/intimm/7.4.525
|View full text |Cite
|
Sign up to set email alerts
|

Co-activation of naive CD4+ T cells and bone marrow-derived mast cells results in the development of Th2 cells

Abstract: Activation of naive dense CD4+ T cells by plate-bound anti-CD3 antibodies favors the development of Th1 cells which, upon re-stimulation, produce significant amounts of IFN-gamma but no IL-4. However, co-activation of such naive T cells in the presence of IgE [anti-dinitrophenyl (DNP)]-loaded bone marrow-derived mast cells (BMMC) on plates coated with anti-CD3 antibodies and DNP-BSA led to the development of IL-4-producing Th2 cells. The same result could be observed if irradiated (800 rad) BMMC were applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 0 publications
2
34
0
Order By: Relevance
“…Mast cell-derived cytokines have numerous effects on other cells of the immune system as well as endothelial cells. For example, mast cell-derived cytokines can cause B cells to class switch to synthesize IgE, induce basophil histamine release, recruit neutrophils and eosinophils, and promote the development of T cells into a T helper 2 (Th2) phenotype [17][18][19].…”
Section: Role Of Mast Cells In Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell-derived cytokines have numerous effects on other cells of the immune system as well as endothelial cells. For example, mast cell-derived cytokines can cause B cells to class switch to synthesize IgE, induce basophil histamine release, recruit neutrophils and eosinophils, and promote the development of T cells into a T helper 2 (Th2) phenotype [17][18][19].…”
Section: Role Of Mast Cells In Inflammationmentioning
confidence: 99%
“…In addition to the effects mast cells directly exert on the pathogenesis of asthma, they also have the ability to contribute to the initiation of Th2 responses by the production of IL-4 and IL-13 [18]. Recently, thymic stromal lymphopoietin (TSLP), released by epithelial cells in response to physical injury and/or inflammatory cytokines, has been reported as a possible initiator of asthmatic responses through the potent stimulation of mast cells, to produce high levels of Th2 cytokines [51].…”
Section: Asthmamentioning
confidence: 99%
“…During the early phase (i.e., within hours of UV exposure) an IL-10-producing suppressor B cell is activated (18,19), followed a few days to weeks later by CD4 ϩ regulatory T cells (4,20,21). Mast cells are not only potent B cell activators (22,23), they are capable of producing Th2-polarizing cytokines (24) that preferentially activate CD4 ϩ Th2 cells (25). Most of these earlier studies used in vitro-cultured BMMC and therefore it is still not clear exactly how a mast cell in the periphery influences lymphocyte activation, although their ability to reach draining lymph nodes (DLN) where lymphocyte activation occurs would seem to be a necessary prerequisite.…”
mentioning
confidence: 99%
“…6,7 In turn, it has been shown that activated T cells can induce in vitro histamine, TNF-␣, matrix metalloproteinase-9 secretion, and interleukin 4 (IL-4) mRNA expression in mast cell subsets. [16][17][18] Finally, mast cells have been reported to promote in vivo T-cell migration to inflammatory sites by secreting chemotactic factors, such as lymphotactin and IL-16 19 and to orient Th differentiation via the production of 21 Taken together these studies highlight the existence of functionally important mast cell/T-cell crosstalk and raise the question of whether mast cell/T-cell cognate interactions might occur in the course of immune responses.Immunological synapses (ISs) are the morphologic manifestation of the cognate interactions occurring between T cells and other cells of the immune system serving as antigen-presenting cells (APCs). These specialized areas of signal transduction, formed at the T cell/APC contact site, are characterized by large scale clustering and segregation of surface molecules and intracellular signaling components.…”
mentioning
confidence: 99%